The concept of education in the family of the tabligh congregation - Dzaky, Ahmad; Sabda, Syaifuddin; Barni, Mahyuddin (International research journal of management, IT and social sciences, 2021)
A group of people are doing anti-mainstream activities—not doing activities for hedonic things, but willing to sacrifice their energy, thoughts, property, even lives for the sake of Islam. Through peaceful da’wah, this shows that the Tablik congregation has tasted the sweetness of faith in this journey called the Jamâ’ah Table. The main problem is what is the concept of education in the Tablighi Jamaat family? Through a phenomenological approach, we developed this study in a qualitative design. The findings include the description of the concept of education based on objectives, dominant educational institutions, curriculum content, methods, and evaluations. The purpose of tablik family education is to make their children as da’i in the perspective of Jamâ’ah Tablighi. The dominant educational institutions are Islamic boarding schools affiliated with the Tablighi Jamaat. The curriculum content is in the form of religious material, namely faith, the Koran, shari’a science, the formation of the character of the preacher, and the science of fadhilah. Educational methods include methods of internalization, example, dialogue, habituation, stories, muhasabah, and methods of God’s help.